PENGARUH KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI WILAYAH KABUPATEN TANGERANG - Diki Ruspendi; Rudy, Rudy (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to determine the effect of taxpayer awareness, tax sanctions, and service quality on motor vehicle taxpayer compliance. The population in this study were motor vehicle taxpayers who paid vehicle tax at the Pasarkemis SAMSAT outlet. The variables used in this study were taxpayer awareness (X1), tax sanctions (X2), service quality (X3), and motor vehicle taxpayer compliance (Y). This type of research uses a quantitative method with a descriptive approach. The results of this study indicate that taxpayer awareness has an effect on motor vehicle taxpayer compliance, while tax sanctions have an effect on motor vehicle taxpayer compliance, and service quality has an effect on motor vehicle taxpayer compliance. Simultaneously, taxpayer awareness, tax sanctions, and service quality have an effect on motor vehicle taxpayer compliance